Edukasi Diet Rendah Garam dan Pembatasan Cairan terhadap Self Efficacy dan Motivasi untuk Sembuh pada Pasien Hemodialysis (Journal of Telenursing (JOTING), 2024)
This study aims to determine low salt diet education and fluid restriction on self-efficacy in controlling fluid salt intake and motivation to recover in haemodialysis patients. The method used in this research is quasi-experimental research. This quasi-experimental uses a Non Equivalent Control Group design or often called Non Randomised Control Group Pretest And Posttest Design. The results showed that based on the results of the Dependent T Test there was a difference in Self Efficacy before and after education in the intervention group with a p-value of 0.001